Design Study of High Performance Steam Propulsion System for LNG Carrier - Siow, C.L. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2013)
This paper was discussed the current possibility technology can be used to design a high performance steam propulsion system for an LNG carrier. The propose system was designed based on the available technology for marine industry. The technical performance analysis was carried out to evaluate the improvement of the system. Economic performance for this system was also discussed in paper. The sensitivity analysis used for the economic performance analysis was made by varying the relative system initial cost and fuel price to cover several possible economic conditions to operate LNG Carrier.